Evaluating the impact of an arts-based multimedia knowledge translation assignment on undergraduate nursing students. (October 2021) - Rieger, Kendra L.; Mitchell, Kim M.; Bolianatz, Josie; Rabbani, Rasheda; Harder, Nicole; Balneaves, Lynda G.; Armah, Naomi; Martin, Donna
Abstract: Background: Despite the expectation that nurses utilize research to provide excellent patient care, students often fail to recognize the value of learning about evidence-informed practice. Experiential, creative pedagogical approaches are needed to engage undergraduate nursing students in evidence-informed practice. In two undergraduate courses, we implemented an innovative assignment in which students created an arts-based multimedia knowledge translation presentation to communicate systematic review findings to patients. Objective: To evaluate how the assignment affected nursing students' satisfaction, learning, and anticipated behaviour changes regarding evidence-informed practice and to assess what factors influenced their evaluation of the assignment. Design and methods: Kirkpatrick's Evaluation Model and Groff's Theory of Whole-Mindedness informed our study, incorporating an observational cross-sectional survey design. We recruited a convenience sample of nursing students ( N = 242) from two baccalaureate programs. We collected data with an online survey comprised of closed- and open-ended questions. Quantitative data were analyzed with descriptive statistics, univariate analysis, and general linear models, and qualitative data with content analysis. Results: Most students were satisfied (68%) and reported learning (77%) and benefits for their future practice (75%). Age, enjoyment of and experience with the arts, type of motivation, and valuing evidence-informed practice were significant predictors ( p < 0.01) and the model predicted 59% of the variance in positive student perceptions of the assignment. Students reported experiencing relational and engaged learning, translating research findings creatively and clearly, understanding complex research concepts through experiential learning, and having frustrations and pragmatic concerns. Conclusion: Creative approaches that contextualize research findings hold potential to deepen students' understanding of evidence-informed practice. This study identified key factors that influenced students' evaluation and experience of the assignment. These results provide valuable insights to inform effective implementation of arts-based assignments in nursing education.